Information Retrieval from Bibliographic Databases on CD-ROMs in Forestry - Ray, Malabika (Indian Forester, 1997)
This article describes some important tools and techniques for searching bibliographic databases on CD-ROMs and floppy diskettes. It also demonstrates how specific queries can be formulated for retrieving information from electronic documents through use of search operators and specific vocabulary from a thesaurus. The author emphasizes that the users of information actually query the databases themselves in order to satisfy their information needs.